HISTORICAL ASPECTS OF PHALLOPLASTY - P. S. Kyzlasov; M. M. Sokol'shchik; A. A. Kazhera; M. V. Zabelin (Исследования и практика в медицине, 2017)
Reconstruction of the penis in transgender operations, amputation of the penis, congenital deformities and anomalies of the penis was and remains today an important issue in plastic surgery of the urogenital region. The only method to restore the penis is phalloplasty. In general, over the past decades, generations of clinicians have different ways and flaps for total fallouretheral reconstruction. Thus was formulated the characteristics of an ideal flap for the formation of neophallos, which should be safe, sensitive, without hair, and with long leg. However, despite the fact that the characteristics of a perfect flap, nowadays there is no “gold standard” in the formation of neophallos, as phalloplasty is a fairly complicated surgery, and the choice of method depends on many factors. The choice of methodology is determined by the plastics surgeon and to each patient is individual, depends on the etiology of the disease and the possibility of choosing the form of the donor’s transplant. This article presents a literature review devoted to the historical aspects of phalloplasty. In the article, in chronological order reflected the evolution of the different forming methods neofallos, phallourethrоplasty, describes their advantages and disadvantages.